Free convection in porous media filled right-angle triangular enclosures - Varol, Yasin; Öztop, Hakan Fehmi; Varol, Asaf (Pergamon-Elsevier Science Ltd, 2006)
Steady-state free convection heat transfer in a right-angle triangular enclosure, whose vertical wall insulated and inclined and bottom walls are differentially heated, is performed in this study. The governing equations are obtained using Darcy model. In this study, the governing equations were solved by finite difference method and solution of algebraic equations was made via Successive Under Relaxation method. The effect of aspect ratios ranging from 0.25 to 1.0 and Rayleigh numbers 50 <= Ra <= 1000 is investigated as governing parameters on heat transfer and flow field. It is observed that heat transfer is increased with the decreasing of aspect ratio and multiple cells are formed at high Rayleigh numbers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: porous medium; natural convection; triangular enclosure